Technologies and Everyday Life: a Review of Domestication Framework - Sandoval, Luis Ricardo (2022)
Twenty-five years have passed since Roger Silverstone and other researchers proposed domestication —that is, the process by which an animal or plant species is transformed in order to live with humans— as an appropriate metaphor to understand how technological devices are incorporated into people’s daily lives, starting the journey of the technology domestication framework. This proposal was highly productive in theoretical and empirical terms, giving rise to a set of reflections and inquiries and becoming part of the usual background of research on the processes of appropriation of technologies carried out from a sociocultural perspective. In this review, we propose to present the main guidelines of its approach, review the results of the investigations that it has given rise to, and discuss its limits and the necessary adaptations to account for current technocommunicational phenomena.